2000
DOI: 10.1136/ard.59.3.178
|View full text |Cite
|
Sign up to set email alerts
|

Sonography for hip joint effusion in adults with hip pain

Abstract: Objective-To study the prevalence of ultrasonic hip joint eVusion and its relation with clinical, radiological and laboratory (ESR) findings in adults with hip pain. Methods-Patients (n=224) aged 50 years or older with hip pain, referred by the general practitioner for radiological investigation, underwent a standardised examination. The distance between the ventral capsule and the femoral neck, an increase in which represents joint eVusion, was measured sonographically. Joint eVusion was defined in three diVe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 17 publications
1
38
0
3
Order By: Relevance
“…Several clinical studies done in patients with JRA have shown that the knee is the joint most frequently affected 16. History-taking and physical examination supplemented with radiological investigation are the usual tools to make the diagnosis of JRA 17. Radiographic changes mostly represent late and indirect signs of synovial disease 18…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies done in patients with JRA have shown that the knee is the joint most frequently affected 16. History-taking and physical examination supplemented with radiological investigation are the usual tools to make the diagnosis of JRA 17. Radiographic changes mostly represent late and indirect signs of synovial disease 18…”
Section: Discussionmentioning
confidence: 99%
“…È importante ricordare che il costo di un esame US è circa il 10% di quello di un esame RM. L'US rappresenta quindi un'alternativa economicamente vantaggiosa ed altamente indicativa per lo studio delle articolazioni (12,13). Inoltre la tecnica US permette una dettagliata valutazione della cartilagine, possibile nelle piccole articolazioni, e la visualizzazione dei versamenti articolari e dalle proliferazioni sinoviali.…”
Section: Discussioneunclassified
“…L'US si è mostrata particolarmente utile nello studio del sistema muscolo-scheletrico poiché, in aggiunta a quanto ottenibile con le normali tecniche radiografiche, permette di evidenziare la presenza di versamento e di ipertrofia sinoviale e di visualizzare i tessuti molli periarticolari, in particolare le strutture capsulo-legamentose (4). Inoltre, nelle piccole articolazioni, l'esame ecografico può dimostrare alterazioni molto precoci della cartilagine articolare (12). Sebbene l'US muscolo-scheletrica sia normalmente utilizzata per la maggior parte delle articolazioni, poco è stato pubblicato riguardo ad una sua applicazione nello studio dell'anca ed in particolare nell'OA dell'adulto.…”
Section: L'unclassified
“…Joint effusion is diagnosed when the distance between the anterior layer of synovium and the femoral neck is greater than 7 mm, or a difference between both hips is greater than 1 mm [2]. The presence of hip effusion is found frequently in the adults suffering from hip pain [3]. A US-guided aspiration of joint effusion for diagnostic or therapeutic purposes can be performed in this longitudinal-oblique plane along the axis of the femoral neck.…”
Section: Anterior Hip Acetabulum and Hip Joint Recessmentioning
confidence: 99%